Hubungan Peran Guru Dengan Kesehatan Mental Anak Usia Dini di Kota Mataram - Netasya, Baiq Aprilindea; Astini, Baik Nilawati; Rachmayani, Ika; Gunawan, Gunawan (Indonesian Publication Center, 2025)
This study investigates the crucial role of teachers in shaping early childhood mental health during the golden age of development. We aimed to determine if a relationship exists between the teacher's role and the mental health of early childhood students in Mataram City. Employing a quantitative correlational approach, data was collected via questionnaires, observation, and documentation from a random sample of 30 kindergarten teachers in Cakranegara District (from a population of 65). Descriptive analysis revealed that the average teacher role score was